Effects of cumulative school soccer matches separated by 24-h or 48-h interval on physical recovery status of U-19 players - Vitor Hugo Santos Rezende; Diego A. Borba; Lucas A. Souza; Suene F. N. Chaves; Maria H. A. Pinheiro; Hugo C. Martins Costa; Daniel B. Coelho; Rauno A. P. Simola; Carlos M. A. Costa; André Bonadias Gadelha (Universidade Federal de Santa Catarina, 2021)
This study aimed to evaluate the effects of cumulative school soccer matches separated by 24-h or 48-h intervals on recovery status of U-19 players. Thirty-four school athletes (17.6 ± 1.1 years) who played an U-19 school soccer competition (composed of one group with four teams and another group with three teams, followed by semifinals and final) were examined before three matches, which lasted 70 min. Seventeen athletes had 24-h of rest interval between each match (GGG group), while 18 athletes had an interval of 48-h between the second and third matches (GG48hG group). Total Quality Recovery, countermovement jump, 10-m sprint, and maximum lumbar isometric strength were measured. The internal load of each match was calculated by the product of the session Rating of Perceived Exertion and match time. There was a 22% reduction in Total Quality Recovery (p< 0.001) and 12% in 10-m sprint performance (p< 0.001) before the third match in the GGG group, while the GG48hG group did not show changes for the same variables (p> 0.05). The countermovement jump decreased before the second match in both groups (GGG= 12% and GG48hG= 10%; p< 0.001), with no difference between groups (p> 0.05). In addition, both groups did not show changes in the isometric strength and in the internal load match over the games (p> 0.05). Despite not providing a complete muscle recovery, 48-h interval between the second and third matches seems to have minimized the effect of consecutive matches in muscle performance reduction.